Microbiological, Nutritional, and Sensory Quality of Bread Produced from Wheat and Potato Flour Blends - Udeme Joshua Josiah Ijah; Helen Shnada Auta; Mercy Oluwayemisi Aduloju; Sesan Abiodun Aransiola (International Journal of Food Science)
Dehydrated uncooked potato (Irish and sweet) flour was blended by weight with commercial wheat flour at 0 to 10% levels of substitution to make bread. Comparative study of the microbial and nutritional qualities of the bread was undertaken. The total aerobic bacterial counts ranged from 3.0 × 105 cfu/g to 1.09 × 106 cfu/g while the fungal counts ranged from 8.0 × 101 cfu/g to 1.20 × 103 cfu/g of the sample. Coliforms were not detected in the bread. Bacteria isolated were species of Bacillus, Staphylococcus, and Micrococcus while fungi isolates were species of Aspergillus, Penicillium, Rhizopus, and Mucor. The mean sensory scores (color, aroma, taste, texture, and general acceptability) were evaluated. The color of the bread baked from WF/IPF2 (wheat/Irish potato flour, 95 : 5%) blend was preferred to WF (wheat flour, 100%) while WF/SPF1 (wheat/sweet potato flour, 100%) and WF/IPF1 (wheat/Irish potato flour, 90 : 10%) aroma were preferred to WF. However, the bread baked from WF, WF/IPF2 (wheat flour/Irish potato flour, 95 : 5%), and WF/SPF2 (wheat/sweet potato flour, 95 : 5%) was more acceptable than other blends. The use of hydrated potato flour in bread making is advantageous due to increased nutritional value, higher bread yield, and reduced rate of staling.